Fundamental of Entrepreneurship ENT300 : Warm & Cozy Homestay / Hazibullah Napi ... [et al.] - Napi, Hazibullah; Muhd Yusuf, Ain Syarmimi; Hamzah, Nur Batrisyia; Nariman, Mohd Amirrul Akmal; Jamil, Nur Farzana (2015)
A Warm & Cozy Homestay like to promote cultural and natural environmental by letting tourist know their value and the importance, and local genuine attractiveness, under cooperation with the local community. We would like to make a good environment where both tourist and local residents treasure and enjoy local nature environment, and we would like to do our best to ensure that the tourist at one with the natural environment, and we would like to do this by taking special care of the fragile resources of the difference ecosystem. There are criteria and conditions that have to be fulfilled which required the involvement of effoft and precision of giving our service. The demands of the customers are to be recognized in order to satisfy them. This can be achieved by providing good services and different from all other homestay, since customers sometimes demand for something new than what they used to have, When these requirements are fulfilled, the organization then can maximal the profits from the business and increase the number of customers.